Physiologic Timeline of Cranial-Base Suture and Synchondrosis Closure. Issue 6 (26th October 2021) - Vu, Giap H.; Xu, Wen; Go, Beatrice C.; Humphries, Laura S.; Kalmar, Christopher L.; Taylor, Jesse A.; Bartlett, Scott P.; Vossough, Arastoo; Nah-Cederquist, Hyun-Duck; Swanson, Jordan W.
Abstract : Background: Fusion of cranial-base sutures/synchondroses presents a clinical conundrum, given their often unclear "normal" timing of closure. This study investigates the physiologic fusion timelines of cranial-base sutures/synchondroses. Methods: Twenty-three age intervals were analyzed in subjects aged 0 to 18 years. For each age interval, 10 head computed tomographic scans of healthy subjects were assessed. Thirteen cranial-base sutures/synchondroses were evaluated for patency. Partial closure in greater than or equal to 50 percent of subjects and complete bilateral closure in less than 50 percent of subjects defined the fusion "midpoint." Factor analysis identified clusters of related fusion patterns. Results: Two hundred thirty scans met inclusion criteria. The sutures' fusion midpoints and completion ages, respectively, were as follows: frontoethmoidal, 0 to 2 months and 4 years; frontosphenoidal, 6 to 8 months and 12 years; and sphenoparietal, 6 to 8 months and 4 years. Sphenosquamosal, sphenopetrosal, parietosquamosal, and parietomastoid sutures reached the midpoint at 6 to 8 months, 8 years, 9 to 11 months, and 12 years, respectively, but rarely completed fusion. The occipitomastoid suture partially closed in less than or equal to 30 percent of subjects. The synchondroses' fusion midpoints and completion ages, respectively, were as follows: sphenoethmoidal, 3 to 5 months and 5 years; spheno-occipital, 9 years and 17 years; anterior intraoccipital, 4 years and 10 years; and posterior intraoccipital, 18 to 23 months and 4 years. The petro-occipital synchondrosis reached the midpoint at 11 years and completely fused in less than 50 percent of subjects. Order of fusion of the sutures, but not the synchondroses, followed the anterior-to-posterior direction. Factor analysis suggested three separate fusion patterns. Conclusions: The fusion timelines of cranial-base sutures/synchondroses may help providers interpret computed tomographic data of patients with head-shape abnormalities. Future work should elucidate the mechanisms and sequelae of cranial-base suture fusion that deviates from normal timelines.